2021
DOI: 10.14719/pst.1353
|View full text |Cite
|
Sign up to set email alerts
|

Application of moringa leaf extract improves growth and yield of Tomato (Solanum lycopersicum) and Indian Spinach (Basella alba)

Abstract: Moringa (Moringa oleifera L.) leaf extract is a natural plant growth stimulant that is well-known for its ability to improve plant growth and development. A field study was conducted to evaluate the influence of MLE (Moringa Leaf Extract) on the growth, yield and nutritional improvement in two vegetable crops [Tomato (Solanum lycopersicum) and Indian Spinach (Basella alba)]. The extract was applied at two weeks interval with different frequencies. The crops were fertilized with chemical fertilizers and MLE app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 20 publications
0
12
0
1
Order By: Relevance
“…Several studies explored the potential benefits of MLE on improving tomato productivity. This includes studies by Culver et al [44], Mvumi et al [80,90], Ngcobo and Bertling [47] and Hoque et al [81], which found that MLE significantly increased the plant height, leaf number, number of branches, above-ground dry biomass, dry root mass, fruit yield and quality of tomato. The extracts from fresh moringa leaves influenced tomato productivity by augmenting its leaf lamina thickness, stomatal density, stomatal size and fruit yield [80].…”
Section: Effect Of Mle On Tomatomentioning
confidence: 98%
See 2 more Smart Citations
“…Several studies explored the potential benefits of MLE on improving tomato productivity. This includes studies by Culver et al [44], Mvumi et al [80,90], Ngcobo and Bertling [47] and Hoque et al [81], which found that MLE significantly increased the plant height, leaf number, number of branches, above-ground dry biomass, dry root mass, fruit yield and quality of tomato. The extracts from fresh moringa leaves influenced tomato productivity by augmenting its leaf lamina thickness, stomatal density, stomatal size and fruit yield [80].…”
Section: Effect Of Mle On Tomatomentioning
confidence: 98%
“…were considerably increased following foliar MLE application. According to Hoque et al [81], applying MLE can bring immense benefits to the crop produced. Application of aqueous MLE at 100 mL crude extract (100 mL distilled water/1000 g fresh leaves) diluted with 200 mL distilled water resulted in the highest germination percentage, seedling emergence, seedling survival, plant height, dry shoot mass, dry root mass and yield components in sunflower plants (Helianthus annuus L.) [46].…”
Section: Effect Of Mle On Other Plant Speciesmentioning
confidence: 99%
See 1 more Smart Citation
“…Berdasarkan penelitan Kanchani, et al (2019) aplikasi ekstrak daun kelor 10% dengan aplikasi seminggu sekali meningkatkan tinggi tanaman, jumlah cabang, jumlah daun, indeks luas daun, berat kering daun, batang, akar, biomassa total, jumlah polong dan berat kering polong pada tanaman okra (Abelmoschus Esculentus). Hasil penelitian Hoque, et al (2022) pemberian ekstrak Moringa oleifera dapat meningkatkan pertumbuhan, hasil dan serapan hara pada tanaman tomat dan bayam india pada aplikasi ekstrak Moringa oleifera 2 minggu setelah tanam dan setiap 2 minggu sesudahnya. Hasil penelitian lain pada aplikasi ekstrak daun kelor pada 2 minggu setelah berkecambah dan setiap 2 minggu setelahnya dapat meningkatkan tinggi tanaman, jumlah daun, berat basah dan kering serta hasil panen tomat dan kembang kol (Rana, 2019) Penelitian penggunaan ekstrak daun kelor sebagai biostimulan untuk pertumbuhan planlet anggrek hitam tahap aklimatisasi belum pernah dilakukan.…”
Section: Pendahuluanunclassified
“…Modern agricultural sciences are moving towards the use of plant extracts because of their positive effect on vegetative growth characteristics. Plant extracts have been successfully used as organic fertilizers because they contain biologically active compounds that stimulate plant growth and improve nutritional status without harmful effects on many crops [9]. The use of various organic and natural growth stimulants is a suitable way to stimulate plant growth as well as to improve the growth and production of many crops, unlike synthetic stimulants that are more toxic, polluting to the environment and costly [10].…”
Section: Introductionmentioning
confidence: 99%